Workshop report: Summary of feedback on the TAiLS tool - Njuguna, Lucy (International Livestock Research Institute, 2022)
In November 2022, the adaptation tracking team organized workshops with government officials in Kenya and Ethiopia to get feedback on the TAiLS tool. The design of the tool up to this stage was informed by research insights and discussions with various stakeholders on appropriate adaptation tracking indicators. The design was also fundamentally informed by a study of the existing government structures and flows of data on livestock systems. Therefore, the objective of the workshops was to review various aspects of the tool design and to ensure that the tool continues to correspond with user preferences. Separate workshops were organized for Kenya and Ethiopia to support the endeavor to match the tool with country-specific systems and preferences.